Estudios sobre el justiprecio expropiatorio y el derecho - Vignolo Cueva, Orlando; Vignolo Cueva, Gian Carlo (Revista de Derecho, 2019)
This paper presents and explains some issues of the Peruvian expropriation, trying to influence the necessary legal balance that must exist in the treatment and effective deployment of this system. In particular, it highlights the acknowledgment by the Peruvian Legislator of a set of guarantees and limits must respect the State (as a whole) and the subject active promoter of the specific procedure. The guarantees available to the expropriated studied in this article are the valuation and almost forgotten right of revertion of the expropriated property.